Alpheus dentipes Guerin-Meneville 1832 - D'Acoz, Cédric D'Udekem; Degrave, Sammy (Zenodo, 2018)
** Alpheus dentipes Guérin-Méneville, 1832 An eastern Atlantic and Mediterranean species of which a single, small specimen was recorded from Portland Bay (present day Islas Canning), western Patagonia by Miers (1881, as Alpheus sp.) and identified by Coutière (1899) as A. dentipes possibly mislabelled (see Holthuis 1952) or potentially a mis-identification of the more northern, extra-limital Alpheus inca Wicksten & Méndez, 1981. Published as part of D'Acoz, Cédric D'Udekem & Degrave, Sammy, 2018, A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps, pp. 201-240 in Zootaxa 4392 (2) on page 222, DOI:10.11646/zootaxa.4392.2.1, http://zenodo.org/record/1195302